Evidence at source for the mid-fifteenth century eruption of Kuwae, Vanuatu - Chris Ballard; Stuart Bedford; Shane J. Cronin; Sönke Stern (Journal of Applied Volcanology, 2023)
Abstract The mid-fifteenth century eruption of the Kuwae volcano (Vanuatu), known locally as the Tombuk eruption, is widely but not universally considered responsible for one of the three largest atmospheric sulphate events of the past millennium. Questions remain about its precise magnitude and global signature. This controversy reflects a lack of modern description and characterisation of the eruption at source. Through a comprehensive survey of the published and unpublished literature, we review the available historical, archaeological and volcanological evidence for the Kuwae eruption. All sources suggest an eruption with major impacts regionally. The eruption formed a submarine caldera, collapsing the former landmass of Kuwae and leaving two smaller adjacent islands, Epi and Tongoa. On other islands to the immediate south and north, volcanic impacts were variable, enabling survival of refugees from Kuwae, who later recolonised the remnant islands. This review raises hypotheses and questions to be tested through a new multi-disciplinary field research program that aims to establish the precise date and magnitude of the Tombuk eruption, allowing questions of global impact to be addressed with more confidence.